MiR-690, a Runx2-targeted miRNA, regulates osteogenic differentiation of C2C12 myogenic progenitor cells by targeting NF-kappaB p65. Issue 1 (December 2016) - Yu, Shouhe; Geng, Qianqian; Pan, Qiuhui; Liu, Zhongyu; Ding, Shan; Xiang, Qi; Sun, Fenyong; Wang, Can; Huang, Yadong; Hong, An
Abstract Background The runt-related transcription factor 2 (Runx2) is a cell-fate-determining factor that controls osteoblast differentiation and bone formation. It has been previously demonstrated that microRNAs (miRNAs) play important roles in osteogenesis. However, the Runx2-regulated miRNAs that have been reported thus far are limited. In this study, we pursued to identify these miRNAs in Tet-on stable C2C12 cell line (C2C12/Runx2Dox subline). Results Microarray analysis revealed that alterations in miRNA expression occur with 54 miRNAs. Among these miRNAs, miR-690 was identified as a positive regulator of Runx2-induced osteogenic differentiation of C2C12 cells through gain- and loss-of-function assays. Expression of miR-690 is induced by Runx2, which binds directly to the putative promoter ofmir -690 (Mirn690 ). The miR-690 proceeds to inhibit translation of the messenger RNA encoding the nuclear factor kappa B (NF-κB) subunit p65 whose overexpression inhibits Runx2-induced osteogenic differentiation of C2C12 cells. Interleukin-6 (IL-6), a downstream target of NF-κB pathway, is upregulated by p65 overexpression but significantly downregulated during this differentiation process. Furthermore, overexpression of IL-6 impedes the expression ofosteocalcin, a defined marker of late osteoblast differentiation. Conclusions Together, our results suggest that the miR-690 transactivated by Runx2 acts as a positive regulator of Runx2-induced osteogenic differentiation by inactivating the NF-κB pathway via the downregulation of the subunit p65.